PVDF-HFP and 1-ethyl-3-methylimidazolium thiocyanate–doped polymer electrolyte for efficient supercapacitors. (October 2018) - Tuhania, Pankaj; Singh, Pramod K; Bhattacharya, B; Dhapola, Pawan S; Yadav, Shivani; Shukla, PK; Gupta, Meenal
The sole aim of the present article is to develop an ionic liquid (IL)-doped solid polymer electrolyte for an electrochemical double-layer capacitor (EDLC). A solution cast technique was adopted to develop a solid polymer electrolyte of poly (vinylidene fluoride-co-hexafluoropropylene) as host polymer and low-viscosity IL (1-ethyl-3-methylimidazolium thiocyanate) as dopant. Electrochemical impedance spectroscopy measurement showed a six orders of magnitude enhancement in conductivity ( σ ) by IL doping. A linear sweep voltammetric investigation of the electrolyte films exhibited a good electrochemical stability window of 3.6 V. Polarized optical microscopy of the synthesized films revealed a reduction in crystallinity by IL doping. Infrared spectroscopy further affirms the composite nature of the film. The maximum conductivity value of 2.65 mS/cm is obtained for 80% of the ionic-doped system. Using maximum conductivity film and porous carbon-based electrodes, we have developed EDLCs that show a specific capacitance value of 2.36 F/g.